Globalisation and market structure - J. Peter Neary (University College Dublin, Department of Economics, 2002)
This paper reviews some puzzling economic aspects of globalisation and argues that they cannot be satisfactorily addressed in perfectly or monopolistically competitive models. Drawing on recent work, a model of oligopoly in general equilibrium is sketched. The model ensures theoretical consistency by assuming that firms are large in their own markets but small in the economy as a whole, and ensures tractability by assuming quadratic preferences defined over a continuum of goods. Applications considered include the effects of trade liberalisation on industrial structure, on cross-border merger waves, and on the distribution of income between skilled and unskilled workers.
hdl:10197/1306
Keywords: D50; L13; F12; 330; Cross-border mergers; GOLE (General Oligopolistic Equilibrium); market integration; trade and wages; trade liberalisation; Globalisierung; Marktstruktur; Oligopol; Gleichgewichtstheorie; Theorie